Animal Models of Eating Disorders - Avena, Nicole M.; Avena, Nicole M. (Neuromethods,, 2013)
The growth of the field of eating disorder research has led to a vast array of empirical articles, and the development of new animal models that can be used to study these disorders continues to stimulate new research.  Animal Models of Eating Disorders serves as a collection of detailed techniques contributed by experts in the field who are well-versed in the development and implementation of these models. Since eating disorders are complex and likely due to a combination of environmental, genetic, and social causes, the detailed chapters of this volume have been designed to highlight different contributing factors. Collectively, these chapters give a comprehensive and representative overview of both recently developed and classic methodologies used in the study of eating disorders.  Written for the popular Neuromethods series, this work contains the kind of thorough description and implementation advice that promises successful results.   Authoritative and practical, Animal Models of Eating Disorders aims to aid researchers in the use of animal models to assist in their investigation and characterization of the behaviors and neurochemical alterations associated with these devastating disorders.